2017
DOI: 10.1111/ans.13945
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cost of care for tethered versus non‐tethered ureteric stents in the management of uncomplicated upper urinary tract stones

Abstract: It is cheaper to use a tethered ureteric stent compared with non-tethered stents for short-term stenting after uncomplicated URSL, with a mean cost saving of A$864.5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Based on an average 285 km (177 mile) round trip made by patients for cystoscopic stent removal and the cost of driving at $0.15–0.35/km ($0.40–0.90/mile; based on American Automobile Association estimates), Barnes et al [7] estimated a $68–185 saving per patient on travel costs if patients removed their own stents at home. Recently, Okullo et al [21] reported the overall cost of care was (in Australian dollars) a mean (SD) of $3603.6 (1896.7) vs $4468.1 (820.8) ( P = 0.042) for string vs no-string stents, respectively. Such savings may have less impact in smaller countries where distances travelled by patients to their healthcare provider are far less.…”
Section: Discussionmentioning
confidence: 99%
“…Based on an average 285 km (177 mile) round trip made by patients for cystoscopic stent removal and the cost of driving at $0.15–0.35/km ($0.40–0.90/mile; based on American Automobile Association estimates), Barnes et al [7] estimated a $68–185 saving per patient on travel costs if patients removed their own stents at home. Recently, Okullo et al [21] reported the overall cost of care was (in Australian dollars) a mean (SD) of $3603.6 (1896.7) vs $4468.1 (820.8) ( P = 0.042) for string vs no-string stents, respectively. Such savings may have less impact in smaller countries where distances travelled by patients to their healthcare provider are far less.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from avoiding the possible complications related to a cystoscopy, this method can also reduce healthcare-related costs produced by a cystoscopy. An Australian group reported a cost-saving of A$864.5 per case when using tethered stents [121] . There are however concerns of potential dislodgement, discomfort due to the string and risk of developing a UTI.…”
Section: Procedures For Stent Removalmentioning
confidence: 99%